2011
DOI: 10.1021/jp1110899
|View full text |Cite
|
Sign up to set email alerts
|

Cation/Anion Associations in Ionic Liquids Modulated by Hydration and Ionic Medium

Abstract: In order to understand the unique solvation and conduction properties of ionic liquids (ILs), we explore their interionic associations modulated by hydration level and ionic medium. Pulsed-field-gradient NMR allows sensitive measurement of separate cation and anion diffusion coefficients, which combine to reflect ionic aggregation. With increasing hydration of ILs, the anomalous ratio of cation to anion diffusion coefficients reverses, then plateaus to values consistent with expected hydrodynamic radii ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(142 citation statements)
references
References 39 publications
(76 reference statements)
5
137
0
Order By: Relevance
“…In the absence of a concentration gradient, e.g., in equilibrium conditions, we expect that the effective diffusion rate is determined by the amplitude of the potential fluctuations, or "roughness," which universally acts to slow the diffusing particle. 35 The notion of cations diffusing faster in the presence of negatively charged obstacles seems counterintuitive, in light of studies such as from Hou et al, 36 whereby it was shown by pulsed-field nuclear magnetic resonance (NMR) imaging that specific ionic interactions between a diffusing cation and a negatively charged sulfonated surface slowed diffusion. To explain this apparent discrepancy, we resort to a common model of small-molecular diffusion in the presence of buffers that selectively bind a diffuser.…”
Section: B Hse Model With Electrostatic and Van Der Waals Potentialmentioning
confidence: 99%
“…In the absence of a concentration gradient, e.g., in equilibrium conditions, we expect that the effective diffusion rate is determined by the amplitude of the potential fluctuations, or "roughness," which universally acts to slow the diffusing particle. 35 The notion of cations diffusing faster in the presence of negatively charged obstacles seems counterintuitive, in light of studies such as from Hou et al, 36 whereby it was shown by pulsed-field nuclear magnetic resonance (NMR) imaging that specific ionic interactions between a diffusing cation and a negatively charged sulfonated surface slowed diffusion. To explain this apparent discrepancy, we resort to a common model of small-molecular diffusion in the presence of buffers that selectively bind a diffuser.…”
Section: B Hse Model With Electrostatic and Van Der Waals Potentialmentioning
confidence: 99%
“…Extensive research by various groups has established that the use of ionic salts, that is, ILs, composed of heterocyclic diazoles and counter-ions, can substantially improve the transport properties of sulfonated PEMs since the degree of ion dissociation, local concentration of ions, and T g of the membranes can be manipulated. [81][82][83][84] Such manipulations should also cause a large alteration in the thermodynamic properties of the PEMs, leading to an increasing number of fundamental studies on the thermodynamics of ILs-containing sulfonated PEMs. 46 For IL-incorporated sulfonated PEMs, the key factors governing the anhydrous transport properties should be the type of ILs (cations and anions) and the amounts of ILs within the PEMs.…”
Section: Feature Articlementioning
confidence: 99%
“…Due to the volume difference between cations and anions, cathode and anode swell to different extents, thus a volume imbalance is generated in the actuator, which in turn causes a mechanical deformation. Change in the polarity of the electric field reverse the process and direction of bending [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%